On the mechanism of water oxidation by a bimetallic manganese catalyst: a density functional study. - Sameera, WM; McKenzie, C; McGrady, J (2011)
Density functional theory is used to explore possible mechanisms that lead to water oxidation by a bimetallic manganese catalyst developed by McKenzie and co-workers. On the basis of our calculations we propose that the key active intermediate is a mixed valent Mn(III)(μ-O)Mn(IV)-O˙ oxyl radical species, the oxyl centre being the site of nucleophilic attack by water. The mixed-valent species is in equilibrium with an isomeric diamond-core Mn(IV)(μ-O)(2)Mn(IV) structure, which acts as reservoir for the active species. The chemistry appears to be unique to pentadentate ligands because these shift the position of the equilibrium between the Mn(III)(μ-O)Mn(IV)-O˙ and Mn(IV)(μ-O)(2)Mn(IV) isomers, such that significant concentrations of the former are present in solution.